Raf kinase inhibitor protein1 is a myogenic inhibitor with conserved function in avians and mammals. Issue 9 (25th July 2016) - Coulton, Gary; Hou, Yanwen; Mirczuk, Samantha M.; Allen, Steven P.
Abstract : Background: Raf Kinase Inhibitor Protein1 (RKIP) is a tumor suppressor that is present in several adult tissues. It functions as an inhibitor of both Raf/Mek/Erk and NFĸB signaling when unphosphorylated, but following phosphorylation the ability to inhibit Raf/Mek/Erk signaling is lost and RKIP becomes an activator of G‐protein coupled receptor signaling. In neonates and adults, RKIP is known to be expressed in muscle; however, its physiological function is currently unknown.Results: In this study, we show by in situ hybridization and immunofluorescence that RKIP is also expressed in developing chick embryonic muscle, and mouse C2C12 myoblasts. Furthermore, we demonstrate that, in these systems, it functions as an inhibitor of myogenesis: increased levels of RKIP suppress myotube differentiation whereas decreasing RKIP promotes differentiation. Additionally, we show that the ability of RKIP to inhibit myogenesis is dependent upon its phosphorylation state as only the nonphosphorylated form of RKIP suppresses myogenesis.Conclusions: This study, therefore, clearly demonstrates that RKIP has conserved functions as a myogenic inhibitor in both mammalian and avian muscle. Developmental Dynamics 245:902–912, 2016 . © 2016 Wiley Periodicals, Inc.